An extremely rare clinical condition: isolated post-traumatic diaphragmatic injuries - Taskesen, Fatih; Arikanoglu, Zulfu; Onder, Akin; Gul, Mesut; Aliosmanoglu, Ibrahim; Oguz, Abdullah; Celik, Feyzi (Gastroenterology Review/Przegląd Gastroenterologiczny, 2012)
Aim: Isolated post-traumatic diaphragmatic injuries are observed less commonly, and the preoperative diagnosis is difficult to make. Material and methods: Thirteen patients with post-traumatic isolated diaphragmatic injury were treated in our department between January 2005 and June 2011. Age, sex, the cause, the location, the size of rupture, the severity of organ injury, the surgical materials used for repair, the associated morbidity and mortality, and the duration of hospitalization were all evaluated. Results : There were 12 male patients (92.3%) and 1 female patient (7.7%) with an overall mean age of 28.76 years (range: 15-55 years). Blunt trauma was responsible for the injuries in 4 patients (30.8%), while 9 patients (69.2%) had penetrating injuries. The diagnosis was established preoperatively in all patients (100%) via a plain chest X-ray and/or a computed tomography (CT) scan. The location of rupture was on the left side of the diaphragm in 12 patients (92.3%) and on the right side in 1 (7.7%). Isolated post-traumatic diaphragmatic rupture was repaired with interrupted nonabsorbable sutures or polypropylene mesh. Postoperative complications were observed in 2 patients (15.3%). Mortality did not occur in any of our patients. Conclusions: A meticulous physical examination and obtaining a chest X-ray should be the first steps to be taken in patients with suspicious isolated post-traumatic diaphragmatic rupture. In case of uncertainty in diagnosis, advanced modalities such as CT, ultrasonography, and magnetic resonance imaging should be utilized.